Baseline investigation on plasticizers, bisphenol A, polycyclic aromatic hydrocarbons and heavy metals in the surface soil of the informal electronic waste recycling workshops and nearby open dumpsites in Indian metropolitan cities - Chakraborty, Paromita; Sampath, Srimurali; Mukhopadhyay, Moitraiyee; Selvaraj, Sakthivel; Bharat, Girija K; Nizzetto, Luca (Environmental pollution (Barking, Essex, 2019)
Electronic waste (e-waste) has emerged as a global environmental problem because of its massive production volume and un-structured management policy. Since the rate of e-waste accumulation is startling and the combinatorial effects of toxicants are complex, we have investigated six phthalic acid esters (PAEs), bis (2-ethylhexyl) adipate (DEHA)), bisphenol A (BPA), sixteen polycyclic aromatic hydrocarbons (PAHs) and eight heavy metals (HMs) in the surface soil of e-waste recycling workshops and nearby open dumpsites in four metropolitan cities of India viz., New Delhi (north), Kolkata (east), Mumbai (west) and Chennai (south). Average concentration of ∑16PAHs (1259 ng/g), ∑6PAEs (396 ng/g), BPA (140 ng/g) and ∑8HM (1288 mg/kg) in the informal e-waste recycling sites were higher than ∑16PAHs (1029 ng/g), ∑6PAEs (93 ng/g), BPA (121 ng/g) and ∑8HM (675 mg/kg) in dumpsites. Almost 50-90% of BPA, bis (2-ethylhexyl) phthalate (DEHP), ∑7carcPAHs and copper (Cu) were from e-waste sites predominantly from metal recovery sites (EWR). Extensive combustion of e-waste particularly in the EWR sites at New Moore market and Pudupet in Chennai and Wire Lane, Kurla of Mumbai can explain the segregation of diethyl phthalate (DEP), benzyl butyl phthalate (BBP) and carcinogenic PAHs in the first principal component (PC-1). Copper and lead along with highly abundant plasticizers like DEHP, dibutyl phthalate (DBP) and BPA were loaded in PC-2. Combined impact of burning the plastic cables in e-waste and acid leaching process especially at Mandoli in New Delhi might have driven this result. Loading of chrysene, DEHA and low molecular weight (LMW) PAHs mostly in dumpsite soil might have resulted from incomplete combustion of dumped e-waste. Copper was found to exhibit the highest pollution estimated by geo-accumulation index (Igeo). Maximum estimated carcinogenic risk for adults via dermal contact was due to copper, followed by chromium, lead and nickel.
Keywords: polycyklické aromatické uhlovodíky; skládková zařízení; Metals, Heavy; Plasticizers; Indie; Dibutyl Phthalate; Benzhydryl Compounds; Heavy metals; Soil Pollutants; látky znečišťující půdu; dibutylftalát; Phthalic Acids; Recycling; půda; fenoly; Polycyclic Aromatic Hydrocarbons; Cities; recyklace; těžké kovy; Esters; PAHs; elektronický odpad; Waste Disposal Facilities; Phenols; India; Soil; BPA; benzhydrylové sloučeniny; velkoměsta; kyseliny ftalové; Electronic Waste; Electronic waste; změkčovadla; estery